Exploring Trade and Investment Potential Between Indonesia and Slovakia: A Qualitative Analysis - Katon Wicaksono (PT. Publikasiku Academic Solution, 2024)
This study explores the qualitative analysis of the trade and investment potential between Indonesia and Slovakia, two contrasting economies characterized by dynamic differences and untapped economic synergy. Using theories and frameworks from international trade and foreign direct investment, this study aims to give a full picture of the complicated web of economic complementarities, barriers, and policy landscapes that affect the flow of trade and investment between two countries. By conducting a comprehensive examination of existing scholarly works, supplemented by in-depth interviews with experts and focused analysis of specific instances, this study reveals significant areas that are conducive to collaboration as well as the intricate obstacles that hinder commercial transactions. The results underscore the significant impact of legislative frameworks, market entry opportunities, and infrastructure preparedness on the facilitation or impediment of economic participation. Furthermore, the research highlights the necessity of implementing strategic bilateral agreements in order to effectively use the complete range of trade and investment prospects. The conversation expands to include practical consequences for legislators and business professionals, promoting specific measures to reduce obstacles and take advantage of the found economic synergies. This study makes a valuable contribution to the ongoing academic conversation surrounding the improvement of bilateral economic relations by providing a strategic plan for future collaborations between Indonesia and Slovakia.